Mast cell migration from the skin to the draining lymph nodes upon UV-irradiation represents a key step in the induction of immune suppression - Byrne, Scott N. (2008)
The UV radiation in sunlight is the primary cause of skin cancer. UV is also immunosuppressive and numerous studies have shown that UV-induced immune suppression is a major risk factor for skin cancer induction. Previous studies demonstrated that dermal mast cells play a critical role in the induction of immune suppression. Mast cell deficient mice are resistant to the immunosuppressive effects of UV radiation, and UV-induced immune suppression can be restored by injecting bone marrow derived mast cells into the skin of mast cell deficient mice. The exact process however, by which mast cells contribute to immune suppression is not known. Here we show that one of the first steps in the induction of immune suppression is mast cell migration from the skin to the draining lymph nodes. UV-exposure, in a dose dependent manner, causes a significant increase in lymph nodes mast cell numbers. When GFP+ skin was grafted onto mast cell deficient mice, we found that GFP+ mast cells preferentially migrated into the lymph nodes draining the skin. The mast cells migrated primarily to the B cell areas of the draining nodes. Mast cell express CXCR4+ and UV exposure up regulated the expression of its ligand CXCL12, by lymph node B cells. Treating UV-irradiated mice with a CXCR4 antagonist, blocked mast cell migration and abrogated UV-induced immune suppression. Our findings indicate that UV-induced mast cell migration to draining lymph nodes, mediated by CXCR4 interacting with CXCL12, represents a key early step in UV-induced immune suppression.